Neuropsychological deficits in the antisocial personality and their relationship to progress in treatment - Baliousis, Michail (2014)
Background: Antisocial personality is characterised by impulsive behaviour and a pervasive disregard for the rights of others. Its consequences are often debilitating and its presentation poses considerable treatment challenges. While it may be associated with a range of neuropsychological deficits, the literature is often contradictory and no research has examined their effect on treatment.